Suborbital- and millennial-scale monsoon variability during Pleistocene interglacials - Youbin Sun; Ting Wang; Qiuzhen Yin; Steven C. Clemens; Xingxing Liu; Li Ai; Zhipeng Wu; Xiaoke Qiang; Xulong Wang; Hong Chang; Yougui Song; Hendrik Vogel; et al. (Proceedings of the National Academy of Sciences, 2025)
Observational and modeling results show that the frequency and amplitude of extreme climatic events have increased significantly in the context of global warming. However, whether abrupt climate changes intensified during past warm periods remains poorly constrained due to the lack of high-resolution geological records. Here, we report a 512-m predominantly lacustrine sedimentary record from the Weihe Basin (North China), revealing that lake levels fluctuated significantly on suborbital (half- and quarter-precession) and millennial timescales over the last 2 Ma. Grain-size results reveal that magnitudes of rapid lake level fluctuations increased dramatically during Pleistocene interglacials, differing from glacial amplification of abrupt climate events recorded in North Atlantic marine sediments. Model results indicate that summer insolation maxima in low-latitude region of both hemispheres can lead to intensified monsoon precipitation in East Asia. Our proxy-model comparison highlights the importance of low-latitude bihemispheric insolation maxima in driving millennial-scale hydroclimatic variability in a warming future.